Analytical and Early Detection System of Infectious Diseases and Animal Health Status in Kuwait - Al-Hemoud, Ali; AlSaraf, Manar; Malak, Mariam; Al-Shatti, Musab; Al-Jarba, Meshael; Othman, Ahmad; Al-Shammari, Hanadi; Al-Shatti, Alya (Frontiers in Veterinary Science, 2021)
This study aimed at the development of an analytic web-based system for the assessment of animal health in Kuwait. The data sources were based on The World Organization for Animal Health (OIE) and the World Animal Health Information System (WAHIS) repository with data gathered for the period (2005-2020). An on-line web-based system using TABLEAU Creator was developed for monitoring and surveillance of animal disease outbreaks. Five animal diseases were identified in Kuwait; namely, HPAI, FMD, glanders, LSD and MERS-CoV. The highest numbers of outbreaks were recorded for HPAI, followed by FMD. Examples of spatio-temporal visualizations of the web based mappings are presented and include disease cases, number of outbreaks and farm locations, among other features. The web-based system can serve as a monitoring tool to easily display the status of animal health in Kuwait. It can also serve to quickly identify and track disease outbreaks and monitor the spread patterns of new or emerging animal diseases between neighboring countries.